PERIODICITY OF PHANEROZOIC IGENEOUS ACTIVITY IN MONGOLIA, AS EVIDENCED BY POTASSIUM-ARGON DATA - Koval P.V.; Smirnov V.N.; Arakelyants M.M. (My University, 1989)
The potassium-argon method, despite the scepticism it evokes among many geologists because of the many factors potentially capable of distorting the primary isotopic ratios, remains the method most useful in systematic regional investigations of Phanerozoic endogenous minerals. The authors attempted to define the major 'potassium-argon boundaries' of igneous activity in Mongolia, compare these age boundaries with well known theories that postulate the periodicity of such activity, and to evaluate the possibility of using potassium-argon analysis for subdividing and classifying igneous rocks in terms of age. The analysis is based on their own data obtained together with colleagues from the Joint Soviet-Mongolian Expedition, as well as other published data. The most abundant of these are determinations of ages of igneous rocks, mainly granites. Age data on metasomatic rocks (greisens, zwitters, etc.) and ores constituted a small (on the order of 3 percent) fraction of our data.